L'uomo ridotto a una sola posizione. Fame e asservimento ne Le neveu de Rameau di Diderot (Itinera, 2017)
Le neveu de Rameau is a novel that provided many stimuli to philosophers. The dialogue between the two main characters â the philosopher and the servant, the buffoon of the rich and powerful â inspired the Hegelian reflections on the dialectic between servant and master. Le neveu de Rameau is a remarkable representation of the relationships of dependence and negation between those who have power and who is affected by it. The servant is represented as a hungry man, with a knot in his stomach and his mouth open and awaiting; he assumes strained postures which show his subaltern position regarding the master. These bodily figures and behavioral schemes have a relevant ethical and social meaning within the novel: they express the reduction of the complex human unity to a mere condition of need.Â